A New q-Integral Operator Containing Generalized q-Mittag-Leffler Function - Mulugeta Dawud Ali; D. L. Suthar (International Journal of Mathematics and Mathematical Sciences)
In this study, we employ the mathematical framework of q-calculus to introduce a novel integral operator that incorporates the generalized q-Mittag-Leffler function. Following this introduction, we delve into an in-depth analysis of several significant properties and potential applications of this integral operator. Additionally, we explore a number of specific cases to demonstrate the practical utility and implications of our main result.